Resilience of athletes: a systematic review based on a citation network analysis - fonseca bicalho, camila cristina; Ferreira de Melo , Gislane; Noce, Franco (Cuadernos de Psicología del Deporte, 2020)
The aims of the present study are to understand indicators and the scope of theoretical models adopted to describe athletes’ resilience, as well as to analyze their impact on investigations about such resilience. A search for original academic publications within a 10-year period was conducted in the PubMed / Medline, Web of Science, Taylor and Francis, Lilacs, Scopus, Humam Kinects and Science Direct databases, to substantiate a systematic literature review on athletes’ resilience. Articles were analyzed based on their methodological characteristics and citation network analysis. In total, 47 articles were identified and the most referenced one was Fletcher and Sarkar (2012), which was followed by Galli and Vealey (2008). The Grounded Theory of Psychological Resilience and Optimal Sport Performance by Fletcher and Sarkar (2012) seems to encompass the basic theoretical elementary aspects to better understand athletes’ resilience, so far. To conclude resilience is an on-going dynamic process based on individual characteristics and interactions with the environment.